Pengaruh Produksi Beras, Tingkat Kemiskinan, Jumlah Penduduk terhadap Indeks Ketahanan Pangan di Provinsi Kalimantan Selatan: Analisis Data Panel 2018–2024 - Muhammad Saufi; Eny Fahrati (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study investigates the macroeconomic and demographic determinants of the Food Security Index (FSI) in South Kalimantan during the 2018–2024 period. Despite its strategic designation as one of Indonesia’s national food barns, the region faces persistent challenges in stabilizing local food security. Employing panel data regression analysis, specifically the Fixed Effect Model (FEM), this research evaluates the simultaneous and partial impacts of aggregate rice production, poverty rates, and population size on the regional FSI. The empirical findings reveal a critical macroeconomic anomaly: while the selected variables simultaneously influence the food security framework, rice production identified as the most dominant determinant that exhibits a statistically significant negative effect on the FSI. Similarly, the poverty rate demonstrates a significant negative impact, whereas population size remains statistically insignificant. This counterintuitive dynamic, where increased agricultural output paradoxically corresponds with declining regional food security, exposes severe structural bottlenecks within the supply chain. It strongly suggests that agricultural surpluses do not inherently translate into local food availability; rather, output is likely extracted through external market distributions, leaving the local population vulnerable due to constrained purchasing power. Consequently, this study concludes that achieving sustainable food security requires a fundamental policy shift. Rather than relying strictly on an output-centric agricultural paradigm that merely boosts harvest yields, regional policymakers must implement targeted economic interventions prioritizing poverty alleviation, equitable domestic distribution networks, and enhanced economic accessibility for marginalized communities.